Catalyst-free one step synthesis of large area vertically stacked N-doped graphene-boron nitride heterostructures from biomass source. Issue 9 (16th February 2018) - Esteve-Adell, Ivan; He, Jinbao; Ramiro, Fernando; Atienzar, Pedro; Primo, Ana; García, Hermenegildo
Abstract : A procedure for the one-step preparation of films of few-layer N-doped graphene on top of nanometric hexagonal boron nitride sheets based on the pyrolysis at 900 °C under an inert atmosphere is reported. Abstract : A procedure for the one-step preparation of films of few-layer N-doped graphene on top of nanometric hexagonal boron nitride sheets ((N)graphene/h-BN) based on the pyrolysis at 900 °C under an inert atmosphere of a film of chitosan containing about 20 wt% of ammonium borate salt as a precursor is reported. During the pyrolysis a spontaneous segregation of (N)graphene and boron nitride layers takes place. The films were characterized by optical microscopy that shows a thin graphene overlayer covering the boron nitride layer, the latter showing characteristic cracks, and by XPS measurements at different monitoring angles from 0° to 50° where an increase in the proportion of C vs. B and N was observed. The resulting (N)graphene/h-BN films were also characterized by Raman, HRTEM, SEM, FIB-SEM and AFM. The thickness of the (N)graphene and h-BN layers can be controlled by varying the concentration of precursors and the spin coating rate and is typically below 5 nm. Electrical conductivity measurements using microelectrodes can cause the burning of the graphene layer at high intensities, while lower intensities show that (N)graphene/h-BN films behave as capacitors in the range of positive voltages.